Untargeted metabolomic profiling of three Crataegus species (hawthorn) and their in vitro biological activities - ŞENKARDEŞ, İSMAİL (WILEY, 2020)
BACKGROUND In this investigation, the chemical and biological profiles of three Turkish Crataegus species (Crataegus orientalis, Crataegus szovitsii and Crataegus tanacetifolia) were studied in order to provide the first comprehensive characterization and their health-promoting potential. In this respect, polyphenolic profiles were evaluated using ultrahigh-performance liquid chromatography-quadrupole time-of-flight mass spectrometry. The in vitro antioxidant activities of the Crataegus samples were evaluated by using free-radical scavenging, phosphomolybdenum, ferrous-ion chelating, and reducing power assays. The inhibitory activities against alpha-glucosidase, amylase, cholinesterases (acetylcholinesterase (AChE) and butyrylcholinesterase (BChE)), and tyrosinase were also established. RESULTS The untargeted metabolomic approach highlighted the effect of both extraction types and species on the phenolic profiles of different Crateagus tissues (i.e. leaves and twigs). The methanolic extracts showed the maximum radical scavenging and reducing activity in all test systems, whereas for ferrous-ion chelating assays the decocted and infused extracts showed the highest activity. Only the methanolic extracts were effective against AChE and BChE. The extract tested showed remarkable inhibitory effects against tyrosinase and alpha-glucosidase, whereas all the extracts exhibited modest inhibition against alpha-amylase. Overall, the twig extracts of the three species studied showed superior antioxidant and enzyme inhibitory activities. CONCLUSION On the basis of these results, the three Crataegus species can be classified as potent bioresources for high-value phytochemicals, which warrant further investigations for developing novel nutraceuticals. (c) 2019 Society of Chemical Industry
Keywords: hawthorn; antioxidant; enzyme inhibitor; phytochemicals; PHYTOCHEMICAL CHARACTERIZATION; POLYMERIC PROCYANIDINS; ANTIOXIDANT ACTIVITY; LEAVES; EXTRACT; FRUIT; INHIBITION; SPP.; GLYCOSIDES; FLOWERS